Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/polym10121396
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Compatibility and Adhesion of Energetic Materials with Several Polymers and Binders: An Experimental Study

Abstract: The chemical compatibility and the adhesion of energetic materials and additive materials exert a strong influence on the sensitivity, safety and performance of a polymer-bonded explosive (PBX). In this study, the chemical compatibility of hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), pentaerythritol tetranitrate (PETN) with several polymers were evaluated using the vacuum stability test (VST) and the differential scanning calorimetry (DSC); while the adhesion between RDX or PETN and each binder based on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…The crystals were aggregated in the RDX-CAB-GBL ink due to the presence of the binder whereas the RDX-GBL ink without a binder showed poor printability, with only a small number of crystals being deposited on the substrate because the amount of RDX precursor was less. The addition of the polymeric binder to the formulation increased the printability of the ink because it allowed the explosive crystals to bind together in a matrix [ 21 , 22 , 23 ]. During the printing of RDX patterns, the solvent continuously evaporated from the printed RDX patterns to form crystalized RDX patterns.…”
Section: Resultsmentioning
confidence: 99%
“…The crystals were aggregated in the RDX-CAB-GBL ink due to the presence of the binder whereas the RDX-GBL ink without a binder showed poor printability, with only a small number of crystals being deposited on the substrate because the amount of RDX precursor was less. The addition of the polymeric binder to the formulation increased the printability of the ink because it allowed the explosive crystals to bind together in a matrix [ 21 , 22 , 23 ]. During the printing of RDX patterns, the solvent continuously evaporated from the printed RDX patterns to form crystalized RDX patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies by Elbeih 36 , et al have investigated the explosive properties of several plastic bonded explosives (PBXs) formulations based on cis-1,3,4,6-tetranitrooctahydroimidazo-[4,5-d]imidazole (BCHMX) in comparison with PETN. Interesting relationships have been achieved between the sensitivity and performance of PETN and several nitramines by Zeman 13,37 , et al PETN has shown obvious changes in its characteristics as a result of the interfacial interactions between its crystals and several materials which clarify its importance to perform PBXs [38][39][40] . Nevertheless, there is still scarcity in studying the optimum polymeric matrix to be used with PETN.…”
Section: Introductionmentioning
confidence: 99%
“…Like all other high-energy materials, the PBX composition is also an unstable thermodynamic system [10]. Compared to the single explosive such as PETN, the thermal decomposition of PBX is generally more complex because of the incompatible reactions between explosives and the polymeric binders [11][12][13][14], and the safety and performance of PBX sample may change during aging.…”
Section: Introductionmentioning
confidence: 99%